2016
DOI: 10.3389/fnut.2016.00032
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Caregiver’s Knowledge, Complementary Feeding Practices, and Adequacy of Nutrient Intake from Homemade Foods for Children of 6–23 Months in Food Insecure Woredas of Wolayita Zone, Ethiopia

Abstract: Complementary feeding should fill the gap in energy and nutrients between estimated daily needs and amount obtained from breastfeeding from 6-month onward. However, homemade complementary foods are often reported for inadequacy in key nutrients despite reports of adequacy for energy and proteins. The aim of this study was to assess caregiver’s complementary feeding knowledge, feeding practices, and to evaluate adequacy daily intakes from homemade complementary foods for children of 6–23 months in food insecure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Also, in that study, the majority of infants following traditional feeding were consuming formula . As a result, pediatricians should emphasize the importance of including iron‐rich food sources in infant diets in the complementary feeding period because of the well‐accepted challenges of achieving adequate iron intake at this age, regardless of whether BLW or TSF is being followed …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Also, in that study, the majority of infants following traditional feeding were consuming formula . As a result, pediatricians should emphasize the importance of including iron‐rich food sources in infant diets in the complementary feeding period because of the well‐accepted challenges of achieving adequate iron intake at this age, regardless of whether BLW or TSF is being followed …”
Section: Discussionmentioning
confidence: 94%
“…16 As a result, pediatricians should emphasize the importance of including iron-rich food sources in infant diets in the complementary feeding period because of the well-accepted challenges of achieving adequate iron intake at this age, regardless of whether BLW or TSF is being followed. [27][28][29][30] According to parental report, there was no difference between the two groups in the incidence of choking (BLW, n = 2; TSF, n = 3). The foods that had caused the incident were raw apple (n = 2) and raw carrot (n = 3).…”
Section: Discussionmentioning
confidence: 99%
“…After removing duplicates and screening of titles and articles, 83 studies were selected for full-text review. Eleven primary studies on late initiation of breastfeeding, duration/cessation of exclusive breastfeeding, early initiation of complementary feeding, prelacteal feeding and breastfeeding measurements tools [29][30][31][32][33][34][35][36][37][38][39] and two project reviews [40,41] were excluded from the final analysis.…”
Section: Search Resultsmentioning
confidence: 99%
“…These articles were published between the years 2007 and 2016. Seven studies were conducted in Amhara region [32][33][34][35][36][37][38], two studies in Southern Nations, Nationalities, and Peoples' Region (SNNPR) [30,31], one study in Oromia region [29] and one study in Amhara, Oromia, SNNPR and Tigray regions [38]. Two studies have used EDHS-based data [32,34], eight studies were conducted in urban and rural setting, 10 studies were interviewer administered and one study was prospective study [34].…”
Section: Search Resultsmentioning
confidence: 99%
“…In addition, a study conducted in Boroujerd (Iran) reported that the knowledge of mothers regarding complementary feeding was 61% and satisfactory [ 24 ]. A study conducted in Ethiopia by Abeshu et al [ 33 ] reported an appropriate maternal knowledge of food security in supplemental nutrition.…”
Section: Discussionmentioning
confidence: 99%